Agricultural imports, agriculture productivity and economic growth in sub-Saharan Africa - Esther N. Mwangi; Fuzhong Chen; Daniel M. Njoroge (Journal of African Trade, 2020)
This study investigates the causal links among agricultural imports, agriculture productivity, and economic growth in 40 sub-Saharan African countries over the period 1990-2015. Granger causality tests are applied to infer direction of causality, and the generalized two-stage least squares instrumental variable technique is employed to estimate the effects while controlling for endogeneity. The bootstrapping procedure is used to deal with cross-sectional dependence. The results reveal bidirectional causality between agricultural imports and agriculture productivity in the full sample, and in middle- and low-income non-oil-exporting countries. The relationship between agricultural imported inputs and agriculture productivity is positive and significant. In addition, unidirectional causality from agricultural imports to economic growth is observed in the full sample and middle-income non-oil exporters. The growth elasticity of agricultural imports is about 1.0 in the full sample and 1.3 in the middle-income group. These results then cast new light on the importance of agricultural imports for growth and development in the African region.
Keywords: C33; C59; Q17; 330; Agricultural import; agriculture productivity; economic growth; Granger causality; Sub-Saharan Africa; Agraraußenhandel; Import; Agrarproduktion; Wirtschaftswachstum; Kausalanalyse; Subsahara-Afrika